2016
DOI: 10.1186/s12918-016-0369-x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of metabolic pathway resources depends on initial enzymatic function assignments: a case for maize

Abstract: BackgroundAs metabolic pathway resources become more commonly available, researchers have unprecedented access to information about their organism of interest. Despite efforts to ensure consistency between various resources, information content and quality can vary widely. Two maize metabolic pathway resources for the B73 inbred line, CornCyc 4.0 and MaizeCyc 2.2, are based on the same gene model set and were developed using Pathway Tools software. These resources differ in their initial enzymatic function ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The most significant biological process enriched for this target gene set is "carboxylic acid metabolic process," which is associated with 16 genes, including the LKR/SDH, cyPPDK1, and cyPPDK2 genes, while the other two enriched biological processes are "glutamine family amino acid biosynthetic process" and "proline catabolic process." Consistent with the GO term enrichments, an analysis of metabolic pathways associated with the O2-activated direct targets using the CornCyc tool (Walsh et al, 2016) revealed genes involved in glycine biosynthesis, l-glutamine biosynthesis, proline metabolism (as part of the l-N δ -acetylornithine biosynthesis pathway), and l-glutamate degradation (Supplemental Data Set 4). Together, these GO term enrichments and pathway associations indicate that O2 directly activates genes encoding storage proteins and enzymes involved in amino acid synthesis and metabolism.…”
Section: O2 Regulates a Diverse Set Of Genes Involved In Endosperm Stsupporting
confidence: 52%
“…The most significant biological process enriched for this target gene set is "carboxylic acid metabolic process," which is associated with 16 genes, including the LKR/SDH, cyPPDK1, and cyPPDK2 genes, while the other two enriched biological processes are "glutamine family amino acid biosynthetic process" and "proline catabolic process." Consistent with the GO term enrichments, an analysis of metabolic pathways associated with the O2-activated direct targets using the CornCyc tool (Walsh et al, 2016) revealed genes involved in glycine biosynthesis, l-glutamine biosynthesis, proline metabolism (as part of the l-N δ -acetylornithine biosynthesis pathway), and l-glutamate degradation (Supplemental Data Set 4). Together, these GO term enrichments and pathway associations indicate that O2 directly activates genes encoding storage proteins and enzymes involved in amino acid synthesis and metabolism.…”
Section: O2 Regulates a Diverse Set Of Genes Involved In Endosperm Stsupporting
confidence: 52%
“…We compiled a list of genes pertinent to glycerolipid metabolism starting with a search of all genes belonging to the Zea mays ‘Glycerophospholipid metabolism’ and ‘Glycerolipid metabolism’ KEGG pathways (98) (map identifiers: zma00564 and zma00561). With the NCBI Entrez gene identifiers in KEGG we retrieved the AGPv4 transcript identifiers used in Corncyc 8.0 (99; 100) from an id cross reference file found in MaizeGDB (99). This resulted in a list of 300 genes comprising 51 Corncyc pathways.…”
Section: Methodsmentioning
confidence: 99%
“…CornCyc (39,40) is a pathway-genome database developed by the Plant Metabolic Network (PMN) in collaboration with MaizeGDB. The current version 9.0 was built using the B73 RefGen_v4 assembly and Pathway Tools v22.0 (41).…”
Section: Interface and Data Updatementioning
confidence: 99%